The Effect of Discipline on the Performance of Firefighters (PKP-PK) at Adi Sumarmo Airport in Solo - Erdin Setiawan; Hodi Hodi (CV. Rayyan Dwi Bharata, 2023)
Airports have long been considered as the entrance to an area, region, and even a country, besides that airports also have officers according to their respective units. Flight Accident and Fire Fighting Assistance (PKP-PK) is part of the crisis management unit at the air terminal which has a special office for PKP-PK vehicles, functional devices and PKP-PK supporting materials as well as faculty supplies on each flight. terminal to provide accident assistance. The type of examination used in this research is a special research using a quantitative methodology. The results of this study show that the consequences of the speculation test results in the review show that the effect of variable X (reasonable) on factor Y (execution) shows solid results by obtaining a connection coefficient of 0.677 in the form of a guarantee coefficient of 45.8% with a remainder of 52, 8% is influenced by various factors that are not checked by specialists such as possibility, responsibility, climate and other components. As a result, PKP-PK officers at Adi Soemarmo Solo Airport are disciplined to ensure that their performance in the field is always maintained and improved.